Influence of multi-dimensional environmental knowledge on residents' waste sorting intention: Moderating effect of environmental concern - He, Zhihua; Liu, Yong; Liu, Xiaochun; Wang, Feng; Zhu, Huijia (Frontiers in Psychology, 2022)
The purpose of this study is to explore the impact mechanism of different dimensions of subjective environmental knowledge on the urban residents’ waste sorting intention. The study also explores the moderating role of environmental concern in the relationship between three kinds of subjective environmental knowledge and attitude towards waste sorting. The survey data of Chengdu were analysed by partial least squares regression (N=308). The results show that system knowledge, action-related knowledge and effectiveness knowledge all have positive impacts on residents' attitudes toward waste sorting, and effectiveness knowledge has the most significant impact. Meanwhile, environmental concern positively moderates the relationship between system knowledge, effectiveness knowledge and attitude towards waste sorting. This study has made a significant theoretical dedication to enrich the extant literature on residents’ waste sorting behavior, and provides theoretical insights for the policies-making of government on waste sorting on a practical level.